Diferenciación entre las huellas de Jaguar y puma: un análisis de criterios - Aranda, Marcelo (Instituto de Ecología, A.C., 1994)
This note analyze five criteria used to differentiate between jaguar and puma footprints. Two criteria were The most useful: more pointed toeprints in the puma, and better defined lobes in the heel pads of pumas. One sixth is proposed in this paper, the proportion width of toes at two-thirds of its length divided by the width at one-third of its length. This quantitative criterion is a good discriminator between jaguar and puma footprints, with a confidence limits range from 0.71 to 1.03 in the jaguar and 0.60 to 0.76 in the puma.